Prototype Data Processing System Wide Information Management Using Architectural Design Model View Controller - Iqbal Aurelio Tawakal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
System Wide Information Management is a standard, infrastructure, and governance that enables the management of information related to ATMs and their exchange between qualified parties through interoperable services. SWIM aims to improve interoperability, efficiency, environment, and security and reduce spending. However, in Indonesia itself, the implementation of the Wide Information Management System has yet to be announced, so the exchange of data from ATS Message, Aeronautical, and Meteorological has yet to be fully integrated. Therefore, it is necessary for data processing to integrate some of the information data but still present the main functions listed in the ICAO Doc. 10039 by adapting the Model View Control (MVC) architectural design pattern, which has advantages over conventional ones. To implement the MVC architectural design, we will use the PHP Laravel framework and MySQL database, which is implemented by the functions of SWIM, namely converting raw data, displaying data, converting compressed XML in GZIP format, and being able to exchange data between users. A sending and receiving data simulation will be carried out to exchange data between countries using SWIM Indonesia with Testbench Singapore via the TCP/IP protocol.